2018
DOI: 10.1111/1750-3841.14209
|View full text |Cite
|
Sign up to set email alerts
|

Are Processed Bilberry Products a Good Source of Phenolics?

Abstract: Although we confirmed the common belief among consumers that the consumption of fresh berries is more beneficial than consuming processed products, this study showed that various bilberry-derived products can also be valuable source of phenolic compounds all year round.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In A. alnifolia fruits, too, the same anthocyanin glycosides were confirmed except peonidin‐3‐glucoside, which was not detected (Mazza, ; Ozga et al., ). The procedures of fruit processing had a significant impact on the changed levels of anthocyanins (Lafarga et al., ; Zorenc, Veberic, & Mikulic‐Petkovsek, ). Our results showed that the lowest content of anthocyanins was found in tea and juice (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In A. alnifolia fruits, too, the same anthocyanin glycosides were confirmed except peonidin‐3‐glucoside, which was not detected (Mazza, ; Ozga et al., ). The procedures of fruit processing had a significant impact on the changed levels of anthocyanins (Lafarga et al., ; Zorenc, Veberic, & Mikulic‐Petkovsek, ). Our results showed that the lowest content of anthocyanins was found in tea and juice (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The individual and total contents of flavonols in fruits of V. myrtillus are also presented in Table 1. All the reported studies identified kaempferol, quercetin and myricetin glycosides as the main compounds, although Zorenc et al [2] also reported laricitrin, syringetin and isorhamnetin glycosides [2].…”
Section: Bioactive Compoundsmentioning
confidence: 98%
“…Phenolic compounds are a group of secondary plant metabolites recognized for their health-protective action, namely as an antioxidant [ 2 , 33 ], anti-inflammatory [ 34 ] and antihypertensive [ 35 ], antimicrobial [ 36 ] and anticancer agents [ 37 ]. The fact that V. myrtillus has a high content of phenolic compounds may account for the growing demand for this fruit.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 2 more Smart Citations